HUBUNGAN TINGKAT STRES DENGAN HARGA DIRI REMAJA DI LEMBAGA PEMASYARAKATAN - Liana ' Asnita; Arneliwati ' '; Jumaini ' ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The pupose of this research to determine the relationship between stress levels and self-esteem of adolescents in prison. This research used descriptive correlative design with cross-sectional method. Samples of this research were taken by using total sampling technique. This research sample conducted in prisonclass II B Pekanbaru of 46 adolescents. Data was collected by using Ronsenberg self-esteem (1995) by Ronsenberg and a stress questionnaire was modified by Sulastri (2013). The analysis used kolmogorov-smirnov test. The results showed that adolescents who experience mild stress entirely have high self-esteem were13 respondents (28,3%), and adolescents who experience moderate stress and have high self-esteem were 25 respondents (54,3%). While, the adolescents who have severe stress and have high self-esteem were 5 respondents (10,9%) and the adolescents who have severe stress and have low self-esteem were 3 respondents (6,5%). The result, it can be concluded that there was relationship between stress levels and self-esteem of adolescents in prison (p value 0,025 > α 0,05). Based on this study, it was recommended to prison become as a place for convicts in establishing social relationships with people around, having the good experiences, friendships, and loved. So, the convicts spared of the stress and having high self-esteem. Keywords              : Adolescent, prison, self-esteem, stress levels References            : 75 (2002-2015)